S3_6 Spinning Around - Rhodes, Kira; Doherty, Lauren; Kamran, Aneesah (Physics Special Topics, 2017)
We explore the changing velocity of a pole dancer's spin using a pole which rotates as the performer spins. Assuming the motion is frictionless we find that an initial leg whip perpendicular to the pole lasting pi radians results in a velocity of 0.484 rev/s. By pulling the outstretched leg in to the pole the velocity increases massively to 7.74 rev/s.